P336 The sexual health knowledge, attitudes and behaviour of women living with HIV in banten province, indonesia. (14th July 2019) - Juliastuti, Dyah; Dean, Judith; Fitzgerald, Lisa
Abstract : Background: Among certain communities and nations, the sexual health rights of women living with HIV (WLHIV) are often neglected and considered less important. Social, cultural, and religious believes may restrict safer sexual practices. This study examines the sexual health knowledge, attitude, and practices of WLHIV in Banten Province, Indonesia, and the factors influencing these practices. Methods: A cross-sectional written survey of 209 WLHIV aged 18 to 50 years from seven Banten Province regions, was conducted between May and November 2017 using five peer recruiters. Descriptive and binary regression analysis were performed. Results: The majority were Muslim (87.6%), married (58.9%), and high-school graduated (88.6%). 31.4% experienced intimate partner violence (IPV). 77% had some knowledge of sexually transmitted infection (STI), sourcing information from health care providers (56.9%) and the internet (23.0%). Most believed that a woman could refuse sexual intercourse with their partner because of postpartum/menstruation (78.9%), tiredness/unwillingness (67.7%), partner's STI (64.1%), and his infidelity (62.7%). However, only 49.3% believed that they might refuse sex if the partner opposed condom use. Of the 171 sexually active participants, 78.4% had only one sexual partner. Condoms were the primary contraceptive used; however, 68.4% reported inconsistent condom use which was significantly associated with women's inability to buy condoms (aOR6.54, 95%CI:2.29–18.74), negotiate condom use (aOR6.11%CI:1.69–22.15), and being unmarried (aOR3.04, 95%CI:1.14–8.13). 33.3% self-reported a history/symptoms of STI which was significantly associated with new HIV-diagnosis (aOR=4.53, 95%CI=2.07–9.91), multiple sex-partners (aOR=4.25, 95%CI=1.73–10.43), lack of internet exposure (aOR=4.24, 95%CI=1.55–11.55), IPV (aOR=3.04, 95%CI=1.22–7.55), or unprotected sex (aOR=2.97, 95%CI=1.33–6.60). Conclusion: The sexual health of WLHIV in Indonesia is affected by their relationship status, access to condoms, and ability to negotiate their use. Strategies focused on building a women's capability and support to defend their sexual rights are needed to improve the women's health, facilitate choice and reduce risk of onward HIV transmission. Disclosure: No significant relationships.